2022
DOI: 10.33546/bnj.1931
|View full text |Cite
|
Sign up to set email alerts
|

Relation between socio-demographic factors and professionalism among nurses in Saudi Arabia: A comparative analysis

Abstract: Background: Analyzing how nurses handle professionalism in their careers will help all concerned individuals identify areas of concern to develop and enhance further to achieve or maintain a high degree of professionalism. Objective: This study aimed to determine the level of professionalism among nurses and its differences according to socio-demographic characteristics. Methods: A quantitative cross-sectional approach was utilized in three significant regions of Saudi Arabia. A simple random sampling techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The male participants were all Saudi and senior nurses, which does not reflect the expected demographics in which cohorts are typically non‐Saudi dominated (Alboliteeh, 2022; Albougami et al, 2020; Algamdi, 2022; Table 2). The non‐Saudi cohort of respondents were all under the age of 41, while the Saudis were all, except for one male, younger than 41, this is atypical, with other general nursing studies having the population demographic over 41 at 15.1% (Alshumrani et al, 2022; Table 2).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The male participants were all Saudi and senior nurses, which does not reflect the expected demographics in which cohorts are typically non‐Saudi dominated (Alboliteeh, 2022; Albougami et al, 2020; Algamdi, 2022; Table 2). The non‐Saudi cohort of respondents were all under the age of 41, while the Saudis were all, except for one male, younger than 41, this is atypical, with other general nursing studies having the population demographic over 41 at 15.1% (Alshumrani et al, 2022; Table 2).…”
Section: Resultsmentioning
confidence: 91%
“…The male participants were all Saudi and senior nurses, which does not reflect the expected demographics in which cohorts are typically non-Saudi dominated (Alboliteeh, 2022;Albougami et al, 2020;Algamdi, 2022; Table 2). The non-Saudi cohort of respondents were all under the age of 41, while the Saudis were all, except for one male, younger than 41, this is atypical, with other general nursing studies having the population demographic over 41 at 15.1% (Alshumrani et al, 2022; This survey revealed that junior and senior nursing respondents weakly agree with all statements (Table 3). While neither rank, educational status nor nationality affected the answers of the respondents, there were age, gender and experience effects.…”
Section: R E Su Lt Smentioning
confidence: 83%
“…According to professional development studies, nursing students' professionalism and desire to become nurses are directly associated (Rabie, 2021 ; Shen et al, 2021 ) and is affected by many factors. The professionalism of nurses is affected by factors such as professional identity, turnover intention, nursing education and socio‐demographic (Rabie, 2021 ; Shen et al, 2021 ; Shohani & Zamanzadeh, 2017 ), among which the most prominent factors are self‐determination beliefs and nursing education (Poorchangizi et al, 2019a , Poorchangizi et al, 2019b , Alshumrani et al, 2022 ). At present, researches on the relationship between autonomous belief and professionalism mainly focus on self‐efficacy.…”
Section: Introductionmentioning
confidence: 99%